EFFECT OF BIO-ORGANIC AND MINERAL FERTILIZATION, ON THE GROWTH AND YIELD OF CAULIFLOWER (Brassica oleraceae Var.botrytis) - Ola. M. S. Aldolaimy; H. A. Abdul- Ratha; B. K. Abduljabar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out to study the effect of three factors, the first was biofertilization with four types (without addition, combination of A.brasilense + A. chroococcum combination of G.mosseae + T. harzianum, and combination of the two previous combinations), The second factor four types of organic fertilizer(without adding,vermicompost ,Orgevit, a combination of the two previous organic fertilizers),and the third factor mineral fertilizer with two levels (0% and 50%) of the fertilizer recommendation in addition to the full fertilizer recommendation treatment (second comparison).RCBD was used with three replications. The results showed that the triple interaction of the biofertilization treatments added with the organic fertilizer combination of organic fertilizer with 50% of the mineral fertilizer recommendation showed the highest averages for the characteristics of growth and the total yield, which gave79.740 Mg ha-1, and the content of leaves and the curd from N, P and K after harvest and the content of the soil of N, P and K after harvesting, which amounted to 70.81, 38.19, 370.44 mg kg soil-1,in comparison with the no addition treatment which gave the lowest averages .